Development of high-performance networked polymers based on cyclotrimerization of isocyanates: Control of properties by addition of monoisocyanates - Moritsugu, Masaki; Sudo, Atsushi; Endo, Takeshi (Journal of polymer science. Part A, Polymer chemistry, 2012)
Highly heat‐resistant networked polymers consisting of isocyanurate moieties have been developed based on cyclotrimerization of isocyanates. To the polymerization system using methylene diphenyl 4,4′‐diisocyanate (MDI) as the main component, a series of aromatic monoisocyanates (p‐tolylisocyanate, p‐trifluoromethylphenylisocyanate, p‐tert‐butylphenylisocyanate, and p‐butylphenylisocyanate) were added with varying feed ratio [MDI]0:[monoisocyanate]0 to achieve successful control of flexibility of thecorresponding networked polymers without serious deterioration of the thermal stability.